Children's Views on Their Lives and Well-being : Findings from the Children's Worlds Project - Rees, Gwyther (Children's Well-Being: Indicators and Research, 2017)
This book presents a comprehensive overview of findings from the Children's Worlds project - the most extensive and diverse study to have been conducted globally on children's own views of their lives. It provides a unique comparative insight into the similarities and differences in children's lives and well-being around the world, including findings that challenge prevailing assumptions of where, and in what contexts, children might experience a 'good childhood'. The book draws out the key messages and implications from the study and identifies directions for future work on child well-being. It will be of interest to researchers and students in the field of childhood studies, as well as a wide range of professionals and organisations concerned with improving children's quality of life.